Rekonsiliasi Antarummat Beragama Kristen dan Islam di Ambon Maluku - Tohari, Amin (The Sociology of Islam, 2021)
Religion solves social problems in society, peace is the goal of religion being sent down to the world. However, in reality, religious life cannot be separated from conflicts that result in bloodshed wars. This research examines reconciliation between religious adherents (Christianity and Islam) in the bloody conflict in Ambon, Maluku, 1999-2000. The method used is descriptive-qualitative and social anthropological approaches with a touch of interreligious relations in reconciliation for peace. This research is based on a peripheral Islamic study that emphasizes the locality of the conflict area which is peripheral and local, namely in Ambon. This article is focused on the 20 Wayame Team, which is engaged in interfaith reconciliation efforts in Ambon, which involved two conflicting religious groups (Muslims and Christians). The various reconciliation efforts undertaken by Team 20 include: First, forming equal members from Muslim and Christian elements in one team. Second, actively holding interfaith dialogue in every riot incident in Ambon city as an early evaluation and anticipation. Third, make 4 (four) rules that Christians and Muslims must obey, complete with sanctions and corporal punishment for those who violate them. Fourth, Team 20 actively conducts cross-religious dialogues with residents to detect early outside influences that can create seeds of hostility. Fifth, collaborating with the TNI military as a supervisor and protector of the community from external influences that threaten the stability of peace.